2004
DOI: 10.1111/j.1471-4159.2004.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of plasmalemmal Na+/Ca2+ exchange isoforms to sodium‐dependent calcium influx and NMDA excitotoxicity in depolarized neurons

Abstract: ] c elevations mediated by NCX alone, and NCX plus NCKX combined, were 17 and 6 times more rapid in FNs than in CGCs, respectively. Northern blot analysis showed that FNs preferentially express NCX1 whereas CGCs expressed NCX3. Differences in expression of other isoforms (NCX2, NCKX2, NCKX3 and NCKX4) were less pronounced. We tested whether the NCX or NCKX family of exchangers contributes most to the toxic NMDA-induced Ca 2+ influx in depolarized neurons. We found that in FNs, inhibition of NCX alone was suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 48 publications
3
54
2
Order By: Relevance
“…A prominent contribution by K + -dependent Na + /Ca 2+ exchangers was also recently demonstrated at the mammalian giant presynaptic terminal, the calyx of Held (26). Lastly, consistent with the in situ hybridization studies, NCKX activity has been shown to predominate in hippocampal CA1 neurons, whereas NCX activity predominated in forebrain neurons (24,25). The results of these studies have demonstrated that NCKX proteins play important functional roles in neuronal Ca 2+ signaling, although the precise impact of these exchangers on neuronal function is only beginning to be elucidated.…”
Section: Neuronal Physiologysupporting
confidence: 76%
“…A prominent contribution by K + -dependent Na + /Ca 2+ exchangers was also recently demonstrated at the mammalian giant presynaptic terminal, the calyx of Held (26). Lastly, consistent with the in situ hybridization studies, NCKX activity has been shown to predominate in hippocampal CA1 neurons, whereas NCX activity predominated in forebrain neurons (24,25). The results of these studies have demonstrated that NCKX proteins play important functional roles in neuronal Ca 2+ signaling, although the precise impact of these exchangers on neuronal function is only beginning to be elucidated.…”
Section: Neuronal Physiologysupporting
confidence: 76%
“…Neurons were grown and maintained in culture for 14 -17 days as described previously (8). To monitor Ca 2ϩ fluxes associated with the reverse action of NCKX exchangers, cells were first loaded with the Ca 2ϩ indicator Fura-FF (using the acetoxymethyl ester obtained from Teflabs) and then incubated in 96.7 mM NaCl, 3.6 mM NaHCO 3 , 5 mM KCl, 57.9 mM N-methyl-D-glutamine-Cl, 1.3 mM CaCl 2 , 1 mM MgCl 2 , 10 mM HEPES-Tris, pH 7.4, containing 1 mM ouabain, 10 M nifedipine, 10 M 2,3-dioxo-…”
Section: Methodsmentioning
confidence: 99%
“…The expression of NCKX1 is restricted essentially to retina, whereas NCKX2, NCKX3, and NCKX4 are robustly and broadly expressed with distinct, but overlapping, regional distributions among brain neurons (17). Recent in vitro analysis has revealed an essential role for NCKX in calcium flux in cultured neurons (8,18), and in Ca 2ϩ extrusion from isolated axon terminals, particularly when [Ca 2ϩ ] i reaches M levels or higher (19 -21).…”
Section: Camentioning
confidence: 99%
“…It is reported that inhibition of NKA activity by low concentrations of ouabain leads to increased susceptibility to glutamate excitotoxicity that induces the elevation of intracellular Na ϩ and Ca 2ϩ ions (Brines and Robbins, 1992;Kiedrowski et al, 2004). These observations support our finding that the augmented cell death in Rng105 Ϫ/Ϫ neurons is attributable to the reduced NKA subunit isoforms in dendrites of Rng105 Ϫ/Ϫ neurons.…”
Section: Possible Roles Of Rng105-assocoated Mrnasmentioning
confidence: 99%
“…Three isoforms of the catalytic ␣ subunit, ␣1-3 (McGrail et al, 1991), and among seven isoforms (FXYD1-7) of the ␥ subunit that modulate NKA activity, FXYD1, 6, and 7, are highly expressed in the brain (Geering, 2006), whereas other members of FXYD proteins are expressed in other tissues in a tissue-specific way. Some of the brain-expressed NKA subunits are implicated in neuronal disorders (De Fusco et al, 2003;de Carvalho Aguiar et al, 2004;Deng et al, 2007), which are attributable to the role of NKA [e.g., its role in the propagation of action potentials, defensive roles against excitotoxicity that induces elevation of intracellular concentrations of Na ϩ and Ca 2ϩ ions (Brines and Robbins, 1992;Mark et al, 1995;Kiedrowski et al, 2004), and its roles in postsynaptic functions (Reich et al, 2004;Zhang et al, 2009)]. …”
Section: Introductionmentioning
confidence: 99%